Penerapan Metode Joyfull Learning Berbantukan Media Augmented Reality Untuk Meningkatkan Hasil Belajar Siswa SMA Negeri 1 Kendal Mapel Bahasa Jawa - Fitri Dian Setyorini (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
This research generally aims to improve the learning outcomes of class X-L students of SMAN 1 Kendal for the 2022/2023 academic year by implementing augmented reality-based multimedia learning. And it specifically aims to make students able to achieve learning objectives by producing a minimum KKTP score of 70 and at least 80% of the total students are able to achieve this minimum limit. The research method used in this research is the Classroom Action Research Method or better known as PTK. The CAR method is the process of assessing learning problems in the classroom through self-reflection in an effort to solve these problems by taking planned actions in real situations and analyzing the impact of these treatments. The results of research conducted on class X-L students of SMAN 1 Kendal, the application of Augmented Reality-based learning media with the concept of Joyful Learning can improve student learning outcomes, especially geguritan stinging material. That the application of multimedia presentation learning media can improve student learning outcomes in Javanese language subjects, especially in geguritan's nyerat material.